Community Structure and Composition of Rice Weed (Oryza sativa L.) In Banyubiru Village, Semarang Regency - Haris, Amnan; Ngabekti, Sri (Journal of Environmental and Science Education, 2023)
Weeds are a term used for disturbing plants that live with cultivated plants and if not controlled will reduce the quantity and quality of crop yields. The purpose of this study was to analyze the composition and community structure of weeds in rice aged 8 weeks. The benefits of this research are expected to provide information about the types of weeds and their characteristics. This research was conducted in Banyubiru Village, Semarang Regency; and the Unnes Biology Plant Taxonomy Laboratory. The method used in this study was random sampling using 9 plots measuring 1 m x 1 m. The results showed that there were 11 families, 17 species and 526 individuals with the highest Importance Value Index found in the species Cyperus diiformis L, namely 0.79. The weed diversity index is moderate, namely H' = 1.25.